2017
DOI: 10.14453/aabfj.v11i1.5
|View full text |Cite
|
Sign up to set email alerts
|

IFRS Mandatory Adoption Effect on the Information Asymmetry: Immediate or Delayed?

Abstract: The purpose of this paper is to examine the relationship between the mandatory adoption of IFRS/IAS and the information content of earnings in the European Union. More accurately, this study aims to determine if the effect of IFRS adoption on the level of information asymmetry, apprehended by the cost of capital and the financial analysts' forecasts, is immediate or delayed. Based on a longitudinal study, we find evidence that for the two first years of adoption, international standards reduces significantly t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 37 publications
4
22
2
2
Order By: Relevance
“…Specifically, comparing the pre‐ and post‐adoption of IFRS, the frequency of voluntary disclosure is higher for the post‐IFRS period (2011–2018), while the ratio of split ratings is lower for the post‐IFRS period (2011–2018). These results are consistent with prior studies in that IFRS, principle‐based accounting standards, reduce information asymmetry (i.e., Beneish and Yohn, 2008; Barth et al 2008; Turki et al 2017).…”
Section: Resultssupporting
confidence: 92%
“…Specifically, comparing the pre‐ and post‐adoption of IFRS, the frequency of voluntary disclosure is higher for the post‐IFRS period (2011–2018), while the ratio of split ratings is lower for the post‐IFRS period (2011–2018). These results are consistent with prior studies in that IFRS, principle‐based accounting standards, reduce information asymmetry (i.e., Beneish and Yohn, 2008; Barth et al 2008; Turki et al 2017).…”
Section: Resultssupporting
confidence: 92%
“…They found information asymmetry reduced after IFRS adoption. Finally, Turki et al (2017) same as Armstrong et al (2008) and Preiato, Brown and Tarca (2009) found IFRS/IAS reduces significantly the information asymmetry level in EU countries.…”
Section: Literature Reviewsupporting
confidence: 60%
“…When there is a major change in policy, it is appropriate to test the impacts of that change, such as when the Sarbanes-Oxley Act was introduced [see Lobo and Zhou (2006)], or the adoption of International Financial Reporting Standards (IFRS) [see Callao et al (2007) and Turki et al (2017) for examples]. This is to understand the impacts of changes, intended or otherwise, to make any modifications to policy or practice.…”
Section: Discussionmentioning
confidence: 99%